PEREMPUAN DAN ISU POLIGAMI DI INDONESIA - Lina Kushidayati (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2018)
This article describes the contributions given by Indonesia womento the family laws, especially the issue of polygyny/polygamy. This is a historical research aims at providing a balance perspective on womenresponses upon the enactment of Islamic family law in Indonesia.Despite the socio political condition which limited women‘s role inpublic, Indonesian women were actively contributed to the debateconcerning family law issues, such as polygamy. Arguments given byfemale scholars and activist could not be separated from their sociopolitical background. This is a historical research aims at understandingthe role of Indonesia women in negotiating polygamy in public sphereand their ways of promoting their views and opinions. Data arecollected through library research and then analyzed in order to find thepattern of argumentation and contribution given by women in polygynyissues.